Análises fitotécnicas e anatômicas da enxertia intergenérica de Physalis spp. em solanáceas - Rossi, Maíra Ferreira de Melo (2021)
The species of the genus Physalis, mainly the species P. peruviana, have great productive potential in Brazil. The study of the cultivation and production of these species also includes the propagation methods used. Among these methods, a new possibility is the use of the grafting technique, aiming at the multiplication of the desired species and taking advantage of the benefits of the rootstock. The objective of this work was to evaluate the phytotechnical and anatomical characteristics of the intergeneric grafting of Physalis spp in solanaceous. The research was divided into two experiments, where the first one evaluated the sprouting of five species of Physalis spp. grafted onto a 'Santa Clara I-5300' tomato rootstock. In the second experiment, the compatibility of P. peruviana grafted onto Italian tomatoes, eggplant and jilo was evaluated. The experimental design adopted for both experiments was randomized blocks, containing four blocks and thirty seedlings per parcel. The results showed that the most suitable species for grafting on the tomato (Solanum lycopersicum) rootstock „Santa Clara I-5300‟ are Physalis pubescens, P. angulata and P. peruviana. For the grafting of Physalis peruviana on other solanaceous, the most indicated rootstocks were jilo and eggplant, with the highest percentage of sprouting.